2010
DOI: 10.1111/j.1468-1331.2010.02999.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guidelines on the pharmacological treatment of neuropathic pain: 2010 revision

Abstract: Background and objectives: This second European Federation of Neurological Societies Task Force aimed at updating the existing evidence about the pharmacological treatment of neuropathic pain since 2005. Methods: Studies were identified using the Cochrane Database and Medline. Trials were classified according to the aetiological condition. All class I and II randomized controlled trials (RCTs) were assessed; lower class studies were considered only in conditions that had no top-level studies. Treatments admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
1,166
4
111

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,660 publications
(1,297 citation statements)
references
References 105 publications
16
1,166
4
111
Order By: Relevance
“…This equated to an NNT of 7.05, which is comparable to existing first-line therapies such as high-dose pregabalin (NNT 6.3) (6) and duloxetine (NNT 5) (7). Because opioids are normally a second-line therapy for the management of DPNP, they are often used in combination with first-line therapies (30,31). It is reassuring that the current study demonstrated that buprenorphine patches are effective in patients concomitantly taking antidepressants or antiepileptics.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This equated to an NNT of 7.05, which is comparable to existing first-line therapies such as high-dose pregabalin (NNT 6.3) (6) and duloxetine (NNT 5) (7). Because opioids are normally a second-line therapy for the management of DPNP, they are often used in combination with first-line therapies (30,31). It is reassuring that the current study demonstrated that buprenorphine patches are effective in patients concomitantly taking antidepressants or antiepileptics.…”
Section: Resultsmentioning
confidence: 57%
“…No one therapy is effective for all patients with DPNP, and there is no way to predict which patient will respond to which therapy (5,30). Additional analgesics with robust evidence of clinical effectiveness are needed.…”
Section: Resultsmentioning
confidence: 99%
“…A neuropathic pain case was defined in this study as a type 2 diabetic individual with a history of at least one prescription of any of the following five medicines, which are effective and recommended in diabetic peripheral neuropathy (Attal et al., 2010; Finnerup et al., 2010; NICE, 2013) and used less frequently for other indications: duloxetine, gabapentin, pregabalin, capsaicin cream/patch and lidocaine patch. The cases also had positive monofilament tests in at least one foot, indicating the likely presence of sensory neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…The main symptom is pain; therefore, treatment is symptomatic as recommended by the European Federation of Neurological Societies' guidelines for neuropathic pain [102], with agents such as carbamazepine, gabapentin, and pregabalin (grade 1A). Tricyclic antidepressants may exacerbate sicca symptoms [103], while no immunotherapy has been particularly effective (steroids, IVIg, anti-TNF, or rituximab) [20,88,104,105].…”
Section: Sjögren's Syndromementioning
confidence: 99%